The performance of television broadcasting channel / Nur Hidayah Azman - Azman, Nur Hidayah (2017)
This research paper in conducted to determine the performance of the television broadcasting channel in Malaysia. The performance are measure through the net revenue of the broadcaster as the dependent variable and the factors that may affect it directly or indirectly. The independent variables use in this study are the viewership, the number of television program in a particular channel and last but not least are the number of advertisers in a particular channel. Viewership can easily be define as the audience of a television program. Here, the end product that the researcher want to achieve is to know the relationship between dependent variables and independent variables, either positively or negatively. In this paper, the researcher is using time series monthly basis data for 3 consecutive year which are from January 2014 until December 2016. Data is taken from one of the huge player of television broadcasting industry in Malaysia. For analyzing the data, the researcher uses the Ordinary Least Square (OLS) regression method to stimulate the findings. After regression, the researcher produces the result where two variables have positive relationship with the revenue which are the viewership and the number of advertisers in the particular channel. While the number of program resulted a negative relationship with the revenue. All the findings can be supported by the literature review from the past journal and research that had been provided in chapter two. There are several key terms used in this study, such as free-to-air TV, pay TV, artificial intelligence and many more that are used in this industry.